Fungi traps for animal parasites - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Predatory fungi that capture their prey with sticky 'traps' and 'nets' are being commandeered in the fight against worm parasites of livestock. All over the world, there is an increasing problem of internal parasites in livestock showing resistance...